Measurement and Validation of Entrepreneurial Competency Scale - M.C., MINIMOL (The journal of contemporary issues in business and government, 2021)
The current study is intended to explore the dimensions of entrepreneurial competency construct and the factors that make up each dimension. Entrepreneurial competency is measured in the present study through a survey conducted among small and medium entrepreneurs. Potential indicators are identified from the existing literature. Different researchers use different aspects of competency to track the level of entrepreneurial competency possessed by small and medium entrepreneurs across the world. The existing literature is not providing any evidence of a standardized, validated and self-administered entrepreneurial competency scale. Most of the studies conducted in the field either depends on general competency model or focus on only qualitative aspects of competency.